Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3791/53072
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Culture Expansion of Tumor-specific Endothelial Cells

Abstract: Freshly isolated tumor-specific endothelial cells (TEC) can be used to explore molecular mechanisms of tumor angiogenesis and serve as an in vitro model for developing new angiogenesis inhibitors for cancer. However, long-term in vitro expansion of murine endothelial cells is challenging due to phenotypic drift in culture (endothelial-to-mesenchymal transition) and contamination with non-endothelial cells (EC). This is especially true for TEC which are readily out competed by co-purified fibroblasts or tumor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The membrane‐associated factors ( PLPP3, SDC2, MXRA8 ) identified in our study are of special interest, since they could be used to solve a common problem observed in tissue cultures. Purified cell types of enzymatically digested organs are often contaminated with FBs . The newly identified membrane‐associated FB markers might represent a novel tool to specifically label and remove unwanted FBs from isolated primary cell suspensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The membrane‐associated factors ( PLPP3, SDC2, MXRA8 ) identified in our study are of special interest, since they could be used to solve a common problem observed in tissue cultures. Purified cell types of enzymatically digested organs are often contaminated with FBs . The newly identified membrane‐associated FB markers might represent a novel tool to specifically label and remove unwanted FBs from isolated primary cell suspensions.…”
Section: Discussionmentioning
confidence: 99%
“…Purified cell types of enzymatically digested organs are often contaminated with FBs. 50,51 The newly identified membrane-associated FB markers might represent a novel tool to specifically label and remove unwanted FBs from isolated primary cell suspensions. The feasibility of such an approach merits further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…A major challenge for the universal use of these isolation techniques is the heterogeneity of the endothelial cell population in different vascular beds and the high risk of contamination with fibroblasts and vascular mural cells. However, refinements of the isolation techniques to avoid such contaminations have been reported 24 . Using these techniques, mostly mature endothelial cells are isolated from tissues.…”
Section: Discussionmentioning
confidence: 99%
“…To study the dynamic functions of TECs, it is necessary to use TECs freshly isolated from tumors. Several isolating techniques of TECs from tumors, similar to the methods for isolating the endothelial cells from organs other than tumors (Marelli-Berg et al, 2000;Onoe et al, 2005a;Kajimoto et al, 2010), have been used to elucidate the characteristics of TECs (Amin et al, 2006;Dudley et al, 2008;Matsuda et al, 2010;Xiao et al, 2015). Often, however, we cannot obtain sufficient TECs using these techniques: TECs are indeed a small population within the tumor constituent cells, and their low number does not allow the purification of a sufficient number of cells of high purity.…”
Section: Introductionmentioning
confidence: 99%